2019
DOI: 10.3390/infrastructures4020018
|View full text |Cite
|
Sign up to set email alerts
|

Chloride Penetration at Cold Joints of Structural Members with Dissimilar Concrete Incorporating UHPC

Abstract: This research examines the possibility of enhanced chloride transport at the cold joint incorporating UHPC. The effectiveness of the bond on chloride penetration at the concrete interface with various levels of moisture availability for the substrate at the time of UHPC repair was examined. To this effect, the substrate concrete was conditioned to different moisture content including 0%, 75%, and 100% relative humidity, and soaked prior to UHPC repair concrete casting. Chloride penetration was accelerated by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Other research has been done at Florida International University regarding the chloride penetration, focusing on the effect of corrosion macro cells that can develop between the normal strength concrete (NSC) substrate and the repaired region of the UHPC. Farzad et al [10] states that the repair of concrete elements with UHPC will generally improve the bond strength between two materials, and together with UHPC of low permeability, will result in a more durable structure, improving its service life. This is accomplished by restricting the ingress of damaging agents, improving the sustainability of the repaired structure.…”
Section: System Developmentmentioning
confidence: 99%
“…Other research has been done at Florida International University regarding the chloride penetration, focusing on the effect of corrosion macro cells that can develop between the normal strength concrete (NSC) substrate and the repaired region of the UHPC. Farzad et al [10] states that the repair of concrete elements with UHPC will generally improve the bond strength between two materials, and together with UHPC of low permeability, will result in a more durable structure, improving its service life. This is accomplished by restricting the ingress of damaging agents, improving the sustainability of the repaired structure.…”
Section: System Developmentmentioning
confidence: 99%
“…Reinforced concrete structural components of offshore structures are exposed to corrosion due to the impact of salts and require an analysis of durability indicators to obtain more accurate predictions of the occurrence of corrosion and its course [29]. At the same time, when studying the durability of reinforced concrete, it is important to take into account the effect of chlorides on the corrosion of steel and welds [30,31], taking into account the properties of concrete [31]. There are quite a few studies devoted to the numerical simulation of the transport and diffusion of chlorides in concrete and reinforced concrete elements under cyclic exposure [32,33].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the established desired characteristics of existing commercial repair mortars, the redundancy of their application i.e., the need to re-repair systems has been identified as the reason for high costs. Furthermore, corrosion has also been observed as the commonly reported mortar and concrete deterioration in highways and the pavement industry with repair mortars in place [1,2]. Furthermore, a study revealed that about 20% of the in-place repair mortars have failed within their early periods i.e., 5 years indicating pre-mature damage [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%